English Language Acquisition in Indonesian University Students: The Effect of Learning Styles - Siti Aisah Ginting (ALTSA Publisher, 2022)
The study aims to ascertain whether various forms of learning impact tertiary students' ability to learn the English language. The VARK questionnaire has been chosen as the model for this research (VARK stands for Visual, Aural, Read/Write, and Kinesthetic sensory models used for information acquisition). 100 first-year university students were selected as the respondent in this study. They were required to complete the VARK questionnaire at the start of the study, and the data were analyzed using SPSS. Furthermore, to determine whether the various learning styles correlate with the student's grades throughout the entire course session, the study examined the final results of the students' English examination results. According to the data, students who preferred reading and writing learning styles performed better than those who chose the other. In conclusion, the data gathered are helpful for tertiary educators in the future.